Sensitivity of bank profitability before and after financial crisis / Siti Farhana Shahira Anuar - Anuar, Siti Farhana Shahira (2018)
The profitability of the bank is very important in order for them to rolling up their business. However, the profitability of the banks can be determine by the several factors which is internal and external factors. Internal factors can be come from a bank itself while for the external factors is from the macroeconomic indicators. A good financial system is important for the economic growth (Rachdi, 2013). The aim of this study is to investigate the sensitivity of the bank profitability before (2003 — 2009) and after (2010 — 2016) the financial crisis. The worst financial crisis happened in 2008 (Askari, Shirazi, & Aghababaei Samani, 2018). There are some of the financial institutions suffer from the losses during this financial crisis which need an intervention of the national government to save out the banks (Lai et al., 2014). The measures of profitability that have been used in this study is Return on Asset (ROA). This study will conduct by using a panel data and the sampling for this study is 6 commercial banks in Malaysia which is Maybank, Public Bank, AmBank, RHB Bank, CIMB Bank and Bank Islam.